Nanomedicine: promises and pitfalls 2 - Webster, Thomas J. (Henry Stewart Talks, 2015)
Simultaneous ways to detect & kill bacteria, Determining biofilm and bone formation, Implantable sensor and drug administration, Carbon nanofibers/nanotubes for neural implants, Drug delivery on demand, Stem cells & carbon nanofibers as treatment, Nanomedicine pitfalls, Nanoparticle toxicity, Silver nanoparticles